A Parapsychological Naturalist: A Tribute to Mary Rose Barrington (January 31, 1926 – February 20, 2020) - Weaver, Zofia (Journal of Scientific Exploration, 2020)
Mary Rose Barrington was born in London; her parents were Americans with Polish-Jewish roots who decided to settle in England. By her own account (she very considerately left a biographical note for her obituary writer), her childhood was idyllic, mostly spent riding her pony and playing tennis, as well as reading her older brother’s science fiction. Later she became interested in classical music (she was an accomplished musician, playing cello in a string quartet and singing alto in a local choir) and in poetry, obtaining a degree in English from Oxford University. She then studied law, qualified as a barrister and a solicitor, and spent most of her professional life as a lawyer; her duties included acting as charity administrator for a large group of almshouses. Having a career in the law helped in pursuing two interests of special significance to her, animal protection and the right to voluntary euthanasia. She was responsible for drafting three parliamentary Bills relating to these subjects; none of them passed, but they produced some useful discussions. However, her main interest was in psychical research. When she was 15 she read Sir Oliver Lodge’s Survival of Man, and at Oxford she joined the Oxford University Society for Psychical Research, at that time headed by the philosopher H.H. Price and ran by Richard Wilson, later physics professor at Harvard. The society was very active and hosted knowledgeable invited speakers such as Robert Thouless, Mollie Goldney, and Harry Price. Eventually Mary Rose herself became the Oxford society’s President.